Burn depth assessment in tattooed patients: Diagnostic challenges and potential pitfalls in treatment - Howard Chu; Janak Bechar; Jolita Zakaraite; John Dickson (Wolters Kluwer Medknow Publications, 2022)
Tattoos are commonly accepted as a lifestyle choice, with an estimated 10-20% of the global population having a tattoo. Burn injuries in tattooed skin can be challenging to assess, and incorrect management can lead to an unnecessary burden on resources. This may lead to preventable patient morbidity. We present a case series of patients presenting to our unit with burn injuries on tattooed skin, and discuss recommendations for assessing and optimising care in this cohort. Four male patients aged 23 to 50 years old are discussed in this study, with burn injuries to limb tattooed skin. One patient underwent surgical management and upon a test shave of the apparent full thickness burn with tattoo pigmentation, showed a bleeding dermis which would indicate a more superficial burn. A second patient had burn depth masked a colour tattoo that mimicked a mid to deep dermal burn. We highlight the difficulties in assessing patients with burn injuries in tattooed skin and the importance of ensuring the correct diagnosis in depth of burn. This is to allow optimal treatment and avoid potential complications that may occur as a result of misdiagnosis.